Advent of Cross‐Scale Modeling: High‐Performance Computing of Solidification and Grain Growth. Issue 9 (5th July 2018) - Shibuta, Yasushi; Ohno, Munekazu; Takaki, Tomohiro
Abstract: The application range of computational metallurgy is rapidly expanding thanks to the recent progress in high‐performance computing. In this Progress Report, state‐of‐the‐art collections of large‐scale simulations of solidification and grain growth, performed on the GPU supercomputer, are introduced. One of the notable achievements in this direction is a billion‐atom molecular dynamics simulation for nucleation and solidification, which revealed the heterogeneity in homogeneous nucleation. Moreover, a series of large‐scale phase‐field simulations shed light on the topics at issue including competitive growth of dendrites during the directional solidification, the effect of forced and natural convections on the solidification, and so on. Based on simulation results bridging the gap between atomistic and continuum‐based simulations, a new criterion of multi‐scale modeling is proposed in the age to come. We are now standing at the new era of cross‐scale modeling, in which the overlap between atomistic and continuum simulations creates new research concepts and fields. Abstract : The application range of computational metallurgy is rapidly expanding thanks to the recent progress in high‐performance computing. Here, state‐of‐the‐art collections of large‐scale simulations of solidification and grain growth, performed on the GPU supercomputer, are introduced. Based on simulation results bridging the gap between atomistic and continuum‐based simulations, a new criterion of multi‐scale modeling is proposed in the age to come.